Production of Hydroxy Acids: Selective Double Oxidation of Diols by Flavoprotein Alcohol Oxidase. (4th February 2020) - Martin, Caterina; Trajkovic, Milos; Fraaije, Marco W.
Abstract: Flavoprotein oxidases can catalyze oxidations of alcohols and amines by merely using molecular oxygen as the oxidant, making this class of enzymes appealing for biocatalysis. The FAD‐containing (FAD=flavin adenine dinucleotide) alcohol oxidase from P. chrysosporium facilitated double and triple oxidations for a range of aliphatic diols. Interestingly, depending on the diol substrate, these reactions result in formation of either lactones or hydroxy acids. For example, diethylene glycol could be selectively and fully converted into 2‐(2‐hydroxyethoxy)acetic acid. Such a facile cofactor‐independent biocatalytic route towards hydroxy acids opens up new avenues for the preparation of polyester building blocks. Abstract : Dreifachwirkung : Die Flavoprotein‐Alkoholoxidase (AOX*) vermittelt die Doppel‐ und Dreifachoxidation von Diolen. Je nach Diolsubstrat führen diese Reaktionen entweder zur Bildung von Lactonen oder Hydroxysäuren. Eine solche biokatalytische Route zu Hydroxysäuren hat Potenzial für die Herstellung von Polyesterbausteinen.